215 Sleep duration, quality and timing during confinement amid the COVID-19 Pandemic. (3rd May 2021) - Kaizi-Lutu, Marc; Dinges, David; Cordoza, Makayla; Jones, Christopher; Mange, Ami
Abstract: Introduction: As of March 2020, most U.S. states and territories issued statements advising people "stay at home" to avoid spreading the novel Coronavirus (COVID-19). This resulted in an unprecedented number of people practicing physical confinement and social distancing. This study examined self-reported changes in sleep duration, quality and timing in response to confinement and isolation. Methods: We developed the "Anonymous Survey on Confinement during the COVID-19 Pandemic" to collect information on the American population practicing social distancing and some level of confinement. The survey collected information on demographics, duration and degree of confinement, and sleep-wake dynamics. The online survey was available for completion by any individual ≥18 years of age through the Penn Medicine Clinical Research page from May 16th to November 11th 2020. Descriptive statistics characterized the nature of confinement and non-parametric correlations evaluated the relationships between confinement and sleep-wake dynamics. Results: N=226 participants completed the survey (n=176 female [77.8%]; n=47 male [20.8%]). The average age was 44.9±17.4 years. N=215[95.1%] reported confinement since March 2020 for an average of 89.3±41.7 days in confinement. Surveyed participants in confinement reported sleeping more than before confinement [40.0%], taking the same amount of time to fall asleep [56.6%], and felt that they were getting enough sleep [66.3%]. However, 36.3% of participants reported going to bed earlier and waking up earlier. Participants that engaged in naps prior to confinement reported taking more naps in confinement [50.8%]. Participants reported more daytime sleepiness [42.9%] and more disturbed sleep quality during confinement relative to before confinement [42.5%]. There were no significant correlations between time in confinement and sleep outcomes. Conclusion: During the confinement amid the COVID-19 pandemic, participants responded by sleeping more and at different times, which could reflect circadian disruption of sleep. Changes in sleep amount and sleeping timing were accompanied by increased daytime sleepiness and a reduction in sleep quality. These changes may have been due to age, stressors experienced during the pandemic, social isolation, and/or a change in behavioral routines in response to changing demands and schedules. Our findings suggest that attention to changes in sleep-wake dynamics due to prolonged confinement is likely important to maintain healthy behaviors. Support (if any):